As (re)ações, incertezas e perspectivas dos 'invadidos' com a política de 'pacificação' do complexo da Mangueirinha - Dutra, Leonardo Genaro (2017)
The main objective of this dissertation is to analyze the possible effects on the residents from the 'pacification' process in the Mangueirinha Complex, the only 'pacified' slum outside the urban perimeter of the city of Rio de Janeiro. Located in the Baixada Fluminense, an area with a long history of violence, in Duque de Caxias. UPP Mangueirinha was inaugurated in February 2014, at a time when there was no consensus among several segments of society about this public security policy. Through an ethnography of this 'invisible space' it was possible to understand some aspects of the process of 'pacification' from the perspective of the residents, that is, how they evaluate the whole context of this policy in just over three years of existence.